Conceptualizing Schwartz Values in University Preference Decisions: A Pitch - Asma A. Qureshi (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This reversed engineering pitching letter is an outcome of the course RBUS6914 course studied at The University of Queensland. The letter is written using Faff (2015a) template to present the exploratory relationship personal values of the students and their decisions for making a choice for their university study. The letter includes a brief commentary and personal reflection of the pitching process.
Keywords: M31; 650; personal values; student preference; university; higher education; and pitching research